2013
DOI: 10.12988/ijma.2013.13106
|View full text |Cite
|
Sign up to set email alerts
|

On parameter estimation for Malaysian gold prices modelling and forecasting

Abstract: In developing a time series model, parameter estimation is one of the crucial steps. Common methods of estimation include method of moment (MME), ordinary least square estimation (OLS) and maximum likelihood estimation (MLE). The purpose of the current study is to model and forecast the prices of Malaysian gold called kijang emas using Box-Jenkins methodology. To find the best model, parameter estimates using OLS and MLE were computed. Based on the Akaike information criteria (AIC) and mean absolute percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…ML and LS were compared in [32] to obtain an ARIMA model to predict the gold price. The results reported an error of 0.81% and 2.86% when using a LS and a ML, respectively.…”
Section: Autoregressive Integrated Moving Average Processesmentioning
confidence: 99%
“…ML and LS were compared in [32] to obtain an ARIMA model to predict the gold price. The results reported an error of 0.81% and 2.86% when using a LS and a ML, respectively.…”
Section: Autoregressive Integrated Moving Average Processesmentioning
confidence: 99%
“…The autoregressive integrated moving average (ARIMA) is one of the Box-Jenkins model that is widely applied in research practice for gold price modeling and forecasting, either as a benchmark, comparison, hybrid or forecasting models [4][5][6] [3]. However, a recent study in gold price reported that there is a strong positive trend from 2002 to 2011 that is associated with a higher volatility in that period [7].…”
Section: Introductionmentioning
confidence: 99%
“…An accuracy of the forecasting model is useful to reduce any risk in strategic planning. A forecasting is not only a model [2,4] that employs statistics to formulate the model [5,6,7] such as ARIMA and Holt-Winters but it is also a model that employs machine learning algorithm [3,7] to formulate the model such as Artificial Neural Networks (ANNs) or Support Vector Machine (SVM). An advantage of machine learning model is flexible and convenient for using.…”
Section: Introductionmentioning
confidence: 99%